Novel tigecycline resistance mechanisms in Acinetobacter baumannii mediated by mutations in adeS, rpoB and rrf - Xiaoting Hua; Jintao He; Jingfen Wang; Linghong Zhang; Linyue Zhang; Qingye Xu; Keren Shi; Sebastian Leptihn; Yue Shi; Xiaoting Fu; Pengfei Zhu; Paul G. Higgins; et al. (Emerging Microbes and Infections, 2021)
Acinetobacter baumannii is an important pathogen in hospital acquired infections. Although tigecycline currently remains a potent antibiotic for treating infections caused by multidrug resistant A. baumannii (MDRAB) strains, reports of tigecycline resistant isolates have substantially increased. The resistance mechanisms to tigecycline in A. baumannii are far more complicated and diverse than what has been described in the literature so far. Here, we characterize in vitro-selected MDRAB strains obtained by increasing concentrations of tigecycline. We have identiﬁed mutations in adeS, rrf and rpoB that result in reduced susceptibility to tigecycline. Using in situ complementation experiments, we confirm that mutations in rrf, rpoB, and two types of mutations in adeS correlate with tigecycline resistance. By Western blot and polysome profile analysis, we demonstrate that the rrf mutation results in decreased expression of RRF, which affects the process of ribosome recycling ultimately leading to increased tigecycline tolerance. A transcriptional analysis shows that the mutated rpoB gene plays a role in regulating the expression of the SAM-dependent methyltransferase (trm) and transcriptional regulators, to confer moderate tigecycline resistance. This study provides direct in vitro evidence that mutations in the adeS, rpoB and rrf are associated with tigecycline resistance in A. baumannii.